Impact of Covid-19 On Sustainable Development Goals of Pakistan - FATIMA, SHAHEEN; MUMTAZ, RASHID; FATIMA, SAMREEN; FATIMA, NAUSHEEN (The journal of contemporary issues in business and government, 2021)
Humanity is threatened by COVID-19 since 2019 with severe impact on human economic, social and environmental activities. The spread of pandemic is responsible for creating uncertainty and challenges for developing countries like Pakistan to achieve united nations sustainable development goals. It has a severe impact on every sector of country like tourism, trade, production, health and supply. This study focuses on exploring the impact of COVID-19 on sustainable goals of Pakistan and strategies adopted to cope with this pandemic. SDGs provides guidelines, targets and implementation and financing strategies globally. By having systematic review of already published research articles from various databases were helpful in formulating recommendations to combat the impact of COVID-19 on attaining sustainable development goals. On the basis of available literature and systematic review it is concluded that Covid-19 pandemic has severely affected nations globally economically, socio economically emotionally and had severe impact on achieving sustainable development goals. Factors that create hurdles in achieving sustainable development goals in Pakistan are decline in international trade, decrease in remittances inflow, termination of daily wages jobs, labor immobility in lockdown, decline in production level, supply chain discontinuation, decline in exports and foreign direct investment, projects etc. Several measures were also suggested in light of literature to mitigate the economic impact. This study would be an initiative for future sustainable progress in Pakistan and helpful for developing and implementing strategies and policies so as to combat the severe intensity of COVID-19 that delays the attainment of sustainable development goals in Pakistan.